Revolutionizing Hair Care with Cosmetic Products - Dhanesh, Musale Shreya; Santosh, Bhujbal Rutuja; Naikawadi, Nishigandha D. (Asian Journal of Pharmaceutical Research and Development, 2024)
Over the past 20 years, there has been a significant shift in the hair cosmetics market. The emphasis has shifted drastically from just cleaning to repairing, strengthening, minimizing oxidative damage, and promoting growth. More recent, shorter methods have emerged to give hair a naturally more glossy, silky, and manageable appearance. Over the past 20 years, there has been a significant shift in the hair cosmetics market. The emphasis has shifted drastically from just cleaning to repairing, strengthening, minimizing oxidative damage, and promoting growth. More recent, shorter methods have emerged to give hair a naturally more glossy, silky, and manageable appearance. A variety of hair types, including dry, greasy, colored, and gray hair, can benefit from the cleansing, calming, and conditioning properties of specialized grooming products. [5]Other products, such as hair dyes, relaxers and perms, shampoos, conditioners, and serums, are designed to change the color or composition of the hair shaf Waxes and gels, as well as hair sprays, can change the hair shaft's "lift."Dermatologists are specialists in treating disorders of the scalp and hair, although the cosmetic uses of more recent cosmetic treatments are still undiscovered. With a focus on the Indian market for chemical and "natural" hair products, this research aims to In conclusion, a comprehensive review of hair care emphasizes the importance of individualized routines, considering factors like hair type, concerns, and lifestyle. Quality products, with attention to ingredients and formulations, play a crucial role. Sustainable and ethical practices are increasingly valued by consumers. Regular assessments of personal routines, adapting to seasonal changes, and seeking professional advice when needed contribute to optimal hair health. The evolving landscape of hair care demands a dynamic approach, embracing innovation while prioritizing the well-being of both individuals and the environment. [1]